DISCIPLINE OF VILLAGE APPARATUS IN VILLAGE GOVERNMENT IMPLEMENTATION (Study in Lebak Regency, Banten Province) - Rusito, Rusito (NIAGARA Scientific Journal, 2025)
This writing starts from problems that indicate the low level of discipline of village officials in administering village government in Lebak Regency, Banten Province. The aim of this research is to gain an in-depth understanding of the factors causing low discipline in village officials. The reference used is the opinion of Sutrisno (2010: 89-92) which states that the factors that cause work discipline are compensation, leadership example, definite rules that can be used as a guide, leadership courage in taking action, management supervision, attention to employees and habits. - habits that support the establishment of discipline. The results of the research concluded that the low level of discipline of village officials in Lebak Regency, Banten Province was caused by a compensation system that was not yet performance-based, a lack of exemplary leadership, the absence of technical and operational regulations that could be used as a guide, a lack of leadership courage in taking action, a lack of leadership supervision, There is not yet full attention to village officials and there is not yet a strong organizational culture that supports the upholding of discipline. Key words: discipline, government, village.